A method of determining adsorptive-gas permeability in shale cores with considering effect of dynamic adsorption on flow. (15th May 2020) - Yang, Zehao; Bryant, Steven; Dong, Mingzhe
Abstract: Permeability is an essential parameter in characterizing gas storage and production in shale reservoirs. Most current transient methods for measuring shale permeability use helium instead of methane, which may lead to large errors due to the complexity of gas flow in nanopores of shale. Although some previous studies use methane as the test gas and consider the effect of gas adsorption on permeability measurement, very few studies consider the effect of gas dissolution on measurement. Gas dissolution in organic matter, such as kerogen, may lead to a dynamic adsorption process. This process can delay the gas adsorption equilibrium on kerogen. Investigations on the measurement of radial permeability are also very rare. In this study, a dynamic adsorption-diffusion (DAD) method is proposed to measure gas axial and radial permeability of shale. It presents a new insight into the critical effect of gas adsorption and dissolution on the measurement of permeability of shale. Radial and axial DAD models are based on designed radial and axial DAD experiments with a constant boundary pressure. The exact analytical solutions for these models are further derived to estimate the directional permeability of shale cores. The directional permeability measured by the DAD technique shows a distinct anisotropy for shale. The fitting results of DAD models show it can effectively determine the dominated gas transport in the experiments. The results of the commercial permeameter depict that gas permeability measured using helium can be over 50% larger than that measured using methane. It shows the importance of using methane in the gas permeability measurement of shale in practice.